2013
DOI: 10.1159/000354494
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of the RAGE Affects the Serum Inflammatory Levels and Risk of Ischemic Stroke in a Chinese Population

Abstract: Background: Increasing evidence shows that inflammation plays an important role in the occurrence and progression of acute ischemic stroke. The receptor for advanced glycation end products (RAGE) has been documented to involve in the pathogenic mechanisms of a variety of neurological diseases, including ischemic stroke (IS). However, the impact of RAGE gene polymorphisms on the susceptibility to IS has not been reported. We thus explored the association between RAGE gene polymorphisms and the susceptibility to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…The assumption that the genetic factors contribute to the variation in sRAGE was made in several earlier reports (Gaens et al, 2009;Cui et al, 2013) but this has not been tested using familial data. The studies found that the polymorphisms mapped to the gene encoding RAGE (6p21.3) are significantly associated with sRAGE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The assumption that the genetic factors contribute to the variation in sRAGE was made in several earlier reports (Gaens et al, 2009;Cui et al, 2013) but this has not been tested using familial data. The studies found that the polymorphisms mapped to the gene encoding RAGE (6p21.3) are significantly associated with sRAGE.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific genetic factors responsible for these correlations remain to be established. Genetic variants in the RAGE gene, associated with sRAGE level variation (Cui et al, 2013;Ng et al, 2013), could be the candidate for polymorphisms. On the other hand, genetic polymorphisms in FTO (Prakash et al, 2011;Livshits et al, 2012) and other genes associated with obesity may also contribute to the above correlation.…”
Section: Discussionmentioning
confidence: 99%
“…[19,20] Meanwhile, the role of Gly82Ser polymorphism in IS susceptibility remains controversial. [21,22] …”
Section: Introductionmentioning
confidence: 99%
“…The authors found that the -443CC genotype had higher levels of OPN mRNA compared with other allelic variants and -443C>T variants might influence the OPN mRNA levels via binding of c-Myb transcription factor [33]. In oral squamous cell carcinoma (OSCC) patients, more prevalent -443 T/T genotype was found in OSCC patients [34,35]. Our data showed that -443C>T was significantly related to the gliomas risk.…”
Section: Discussionmentioning
confidence: 70%